Electrochemical corrosion and solid particle erosion response of Y2O3 dispersed FeAl coatings deposited by detonation spray. (April 2023) - Vijaya Lakshmi, D.; Suresh Babu, P.; Rama Krishna, L.; Vijaya Durga, P.; Vijay, R.; Srinivasa Rao, D.
Abstract: The electrochemical corrosion and erosion wear behaviors of detonation sprayed ODS FeAl powder coatings on T91 substrate were investigated. Electrochemical corrosion resistance of the deposited coatings was evaluated in three different aqueous media, namely 3.5 wt% (0.61 M) NaCl, 2 N (1 M) H2 SO4 and 3.5 wt% (0.25 M) Na2 SO4 and are compared with T91 substrate and detonation sprayed Cr3 C2 –25NiCr coatings (on T91 substrate). The ODS FeAl coatings shown improved corrosion resistance in 3.5 wt% Na2 SO4 than T91 substrate. However, the Cr3 C2 –25NiCr coatings have shown consistently better corrosion resistance than T91 substrate and ODS FeAl coatings in all the aqueous media. The corrosion mechanisms investigated imply that the higher corrosion rate of FeAl coatings as compared to the Cr3 C2 –25NiCr coatings is well compensated by the uniform corrosion in the case of former than the localized and intense corrosion in the case of later coatings and substrate material. In contrast, the solid particle erosion wear studies conducted at two different temperatures namely, room temperature (25 °C) and 400 °C have revealed that the ODS FeAl coatings exhibited 4 to 5 times improved wear resistance than that of Cr3 C2 –25NiCr coatings at room temperature and 1.5 to 2.5 times at a higher temperature (400 °C). Also, the ODS FeAl coatings have performed marginally better than the T91 substrate at both the test temperatures. The results obtained together with the observations made demonstrate a leap step towards the development of novel thermal spray grade feedstock materials as an alternative to industrially well-known Cr3 C2 –25NiCr coatings and open up a new avenue of techno-economic benefits that can be further explored. Graphical abstract: Image 1 Highlights: ODS FeAl coatings were developed with in-house synthesized powder using detonation spray. ODS FeAl coatings exhibited hardness values of HV0.3 450, two times higher than steel. Uniform corrosion was noticed in ODS FeAl coatings as against a localized attack in Cr3 C2 –25NiCr coatings. Superior erosion resistance of ODS FeAl coatings indicate their potential applications.